Enterprise 2.0: Identifikasi Faktor Pendorong Adopsi Teknologi Berdasarkan Dimensi Teknologi, Organisasi, Manusia dan Sosial - Handrie Noprisson (JSAI (Journal Scientific and Applied Informatics), 2023)
The challenge of implementing Enterprise 2.0 is the need for budget allocations that must be spent by companies to provide a competitive advantage in the long run. Therefore, several studies propose models of factors influencing the adoption of Enterprise 2.0 technologies. This study aims to answer several research questions about identifying factors driving technology adoption in Enterprise 2.0. The research was conducted with a systematic process to identify, evaluate and interpret all research sources related to the factors driving technology adoption in Enterprise 2.0 based on the database used in this research project is Google Scholar. Based on research data, several factors driving technology adoption in Enterprise 2.0, such as technology, organization, human and social. These factors are influenced by several approaches such as the TOE framework (Technology, Organizational, Environment), UTAUT (The Unified Theory of Acceptence and Use of Technology) and TOS (Technology, Organizational, and Social).